صيغة الإجارة كأداة من أدوات التمويل الشرعي للشركات الصناعية في ليبيا دراسة حالة مصرف التنمية الصناعية في ليبيا = Ijarah formula as a tool of Sharia financing for industrial companies in Libya: case study of the industrial development bank in Libya - Lamari, Ezeddine Mohamed M; Hassan, Aznan; Zakariyah, Habeebullah (Usuli Faqih Research Centre PLT, 2022)
This study aims to clarify the challenges facing the Industrial Development Bank in Libya in applying the leasing formula as a tool of Islamic finance, as well as exploring the credit risks facing the bank in applying the leasing formula. The research problem lies in the lack of Islamic finance programs and formulas by the Industrial Development Bank in Libya to support and finance industrial companies in Libya. The qualitative approach was used in the study, and the case study was adopted as one of the methods of the qualitative approach, in a study by the Industrial Development Bank in Libya. The interview method was used to collect data through interviews conducted with ten employees working in the Central Bank of Libya and the Industrial Development Bank in Libya. The study reached several results, the most important of which is that there is a great need among the employees of the Central Bank of Libya and the Industrial Development Bank in Libya for training and qualification on applying the leasing formula as a tool of Islamic financing for the industrial sector in Libya. Among the results of the study also is that despite the issuance of Law No. 15 of 2010 regulating financial leasing, this law still needs to be amended so that the leasing formula can be applied in Libyan banks in accordance with Islamic Sharia. This study provides a knowledgeable contribution to the sciences related to leasing in international banks in Libya, as well as providing practical knowledge by helping banks operating in Libya to use leasing to finance projects in Libya. The study made several recommendations, the most important of which is the review of Law No. 15 of 2010 and its executive regulations, and the correction of the articles of this law to suit the application of financial leasing mechanisms in accordance with Islamic Sharia, as well as training and qualifying human resources in the Libyan banking sector on the formula of Islamic finance, including leasing in accordance with the provisions Islamic law